NIR-light propelled bowl-like mesoporous polydopamine@UiO-66 metal−organic framework nanomotors for enhanced removal of organic contaminant. (June 2022) - Zhao, Y.; Wang, D.; Luan, Y.; Du, X.
Abstract: Chemical-propelled micro/nanomotors exhibit promising applications in contaminant removal. However, additional hydrogen peroxide (H2 O2 ) often needs to be added to provide chemical propulsion power. Herein, we designed and fabricated a near-infrared (NIR)-light propelled bowl-like nanomotor by the heterogeneous growth of UiO-66 metal−organic framework (MOF) on mesoporous polydopamine (PDA), in order to achieve the enhanced removal of organic contaminant without further addition of any fuel such as H2 O2 . Under light irradiation, the asymmetric nanobowl structure of PDA with high photothermal conversion efficiency can produce an asymmetric thermal gradient field, resulting in self-thermophoretic propulsion. Noteworthily, the motion speed of PDA@UiO-66 nanomotors can reach 18.8 μm/s at the power density of 3 W/cm 2 under 980 nm NIR light irradiation. The PDA@UiO-66 nanomotors show excellent adsorption efficiency of over 78% for methylene blue (MB), and it has a maximum adsorption capacity of 134 mg/g for MB within 40 min under NIR light irradiation. The NIR-light propulsion nanomotors may have potentials in the removal of organic contaminant from the wastewater. Graphical abstract: NIR light-propelled motion nanomotors for the enhanced MB removal. Image 1 Highlights: UiO-66 metal−organic framework nanoparticles are grown on mesoporous polydopamine (PDA) nanobowls. Bowl-like PDA@UiO-66 provides an asymmetric structure for an asymmetric thermal gradient field. The speed of PDA@UiO-66 nanomotors can reach 18.8 μm/s under 980 nm NIR light irradiation. The enhanced directed-motion behavior results in an improved adsorption efficiency and adsorption capacity of methylene blue.